Comparison of Fixation Methods Using a 60°C Hotplate for 10 Minutes, the 2+2 Fixation Method, and the Conventional Method on Rat Liver Tissue - Utami, Ayu Putri; Burhannudin; Najwa Kamila (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
The selection of the optimal method and temperature to accelerate the fixation rate of histological preparations is still ongoing. This study aims to compare the staining quality of histological preparations made by fixation using the 60°C hotplate method for 10 minutes (F60), the 2+2 method (cooling at 4°C for 2 hours and heating at 45°C for 2 hours/FC), and the conventional method (FK). The study used a true experimental posttest-only control group design with liver tissue samples from Wistar rats (Rattus norvegicus) divided into three treatments (F60, FC, and FK). Data processing used the Pearson Chi-Square test. The results of the statistical test showed that there was a significant difference (p < 0.050) in the quality of tissue preparations between the three fixation techniques (conventional, 60°C hotplate, and 2+2). This indicates that the application of a temperature of 60°C for a short time has not been able to produce optimal tissue preparations. This condition is caused by an imbalance in the fixative penetration rate between the outer tissue and the inner tissue, which is faster than the inner tissue. The conventional tissue fixation method used as a control remains the reference.